Genetics of Benign Rolandic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Twenty-two nuclear families with benign epilepsy of childhood with centrotemporal spikes (BECTS, rolandic epilepsy) were analyzed by DNA linkage studies at the Department of Neuropediatrics, University of Kiel, Germany.